Information systems security management key issues in local government - Soares, Delfina de Sá (2014)
Information systems security plays a central role in the provision of services by Public Administration agencies. To foster a trust climate in the development of e-government, it is important to know the main concerns when managing initiatives to protect information assets. The aim of this research in progress is to identify and prioritize the key issues that Local Government chief information officers face, or believe they will face in the near future, in the domain of information systems security management.